Profesionalisme dalam Pendidikan Islam (Studi Literatur) - Wahyudi, Muhammad; Yuliani, Dini; Aura Ningrum, Dwi Ananta (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2024)
Professionalism in Islamic education is one of the important aspects that determine the quality of learning and the achievement of educational goals. This article examines the concept of professionalism in Islamic education with a focus on educator competence, Islamic values, and character-based learning approaches. The professionalism of Islamic educators not only refers to the mastery of knowledge and teaching skills, but also includes moral integrity, appreciation of spiritual values, and the ability to build harmonious relationships with students. This study uses a qualitative approach and a literature review. The research data came from various scientific journal articles on the Google Scholar database. Data analysis is carried out qualitatively, namely descriptive analysis using content analysis techniques. The results of the analysis show that the professionalism of Islamic educators can be achieved through improving pedagogic competence, applying Islamic values in the learning process, and commitment to fostering the character of students. These findings affirm the importance of continuous training and development programs for educators to support the creation of a generation that is not only intellectually intelligent, but also noble in character